The Receiving and Study of Celsian Electrotechnical Ceramics with Innovation One Stage Simplified Technologies in the Bao-Al2O3-Sio2 System - Kovziridze, Zviad; Mshvildadze, Maia; Nizharadze, Natela; Tabatadze, Gulnazi; Darakhvelidze, Nino; Balakhashvili, Maia (European Journal of Applied Sciences, 2022)
Goal: Barite based celsian ceramics with phase composition accordingly (mass%): of celsian 93; Barium Aluminate and Barium Silicate-4; Glass phase - 3, has been synthesized on the bases of local raw materials with single stage innovation technology. Method: One burn at 16000C we have take out from standard technology in which barium carbonate is used. The material displays the best properties in conditions of synthesis at 1410-1460°C Results: Its properties have been studied in complex. The material shows high resistanse to heat shock. A completely new mechanism of ceramic production is proposed. Structure of celsian ceramics in BaO-Al2O3-SiO2 system is studyd with electron microscope, X-ray, crystalline phase content, optical microscope. Water absorbtion, W%=O. Bending strength of non glazed, δ N/mm2 – 69. CLTE, α20-700 106C-1 temperature areas-3.7. Tanget of a dielectric loss angle at 50 Hz and 20°C and tg δ 10-4=107. HV GPa-18.0. Volume resistivity, ρ ohm/cm 200C-3000C=1016-1012. Elastic modulus, E N/mm2-74.5. The process of pores filling, full consolidation of material and hardness growth at comparatively high temperatures of baking interval are studied. Conclusion: High refractoriness of celsian, (1740°C), low thermal coefficient of linear expansion of synthesized materials, high thermal resistivity enable this ceramics to be recommended for introduction in electronical and electrotechnical industry.